Review of the existing maximum residue levels for 2,5‐dichlorobenzoic acid methylester according to Article 12 of Regulation (EC) No 396/2005 - Brancato, Alba (EFSA J, 2018)
According to Article 12 of Regulation (EC) No 396/2005, EFSA has reviewed the maximum residue levels (MRLs) currently established at European level for the pesticide active substance 2,5‐dichlorobenzoic acid methylester. To assess the occurrence of 2,5‐dichlorobenzoic acid methylester residues in plants, processed commodities, rotational crops and livestock, EFSA considered the conclusions derived in the framework of Directive 91/414/EEC as well as the European authorisations reported by Member States. No risk to consumers is expected from the authorised uses. However, due to the lack of data, it was not possible to identify a relevant marker compound and to derive MRLs. Hence, if risk managers would have interest to enforce potential misuses, further data may need to be generated.